Influence of Tillage Method on Management of Amaranthus Species in Soybean. (30th January 2017) - Farmer, Jaime A.; Bradley, Kevin W.; Young, Bryan G.; Steckel, Lawrence E.; Johnson, William G.; Norsworthy, Jason K.; Davis, Vince M.; Loux, Mark M.
Abstract : A field study was conducted in 2014 and 2015 in Arkansas, Illinois, Indiana, Ohio, Tennessee, Wisconsin, and Missouri to determine the effects of tillage system and herbicide program on season-long emergence of Amaranthus species in glufosinate-resistant soybean. The tillage systems evaluated were deep tillage (fall moldboard plow followed by (fb) one pass with a field cultivator in the spring), conventional tillage (fall chisel plow fb one pass with a field cultivator in the spring), minimum tillage (one pass of a vertical tillage tool in the spring), and no-tillage (PRE application of paraquat). Each tillage system also received one of two herbicide programs; PRE application of flumioxazin (0.09 kg ai ha –1 ) fb a POST application of glufosinate (0.59 kg ai ha −1 ) plus S -metolachlor (1.39 kg ai ha –1 ), or POST-only applications of glufosinate (0.59 kg ha −1 ). The deep tillage system resulted in a 62, 67, and 73% reduction in Amaranthus emergence when compared to the conventional, minimum, and no-tillage systems, respectively. The residual herbicide program also resulted in an 87% reduction in Amaranthus species emergence compared to the POST-only program. The deep tillage system, combined with the residual program, resulted in a 97% reduction in Amaranthus species emergence when compared to the minimum tillage system combined with the POST-only program, which had the highest Amaranthus emergence. Soil cores taken prior to planting and herbicide application revealed that only 28% of the Amaranthus seed in the deep tillage system was placed within the top 5-cm of the soil profile compared to 79, 81, and 77% in the conventional, minimum, and no-tillage systems. Overall, the use of deep tillage with a residual herbicide program provided the greatest reduction in Amaranthus species emergence, thus providing a useful tool in managing herbicide-resistant Amaranthus species where appropriate. Abstract : En 2014 y 2015, se realizó un estudio de campo en Arkansas, Illinois, Indiana, Ohio, Tennessee, Wisconsin, y Missouri para determinar los efectos del sistema de labranza y el programa de herbicidas sobre la emergencia de especies de Amaranthus a lo largo de la temporada de crecimiento en soja resistente a glufosinate. Los sistemas de labranza evaluados fueron labranza profunda (arado de vertedera en el otoño seguido por (fb) un pase de cultivador de campo en la primavera), labranza convencional (arado de cincel en el otoño seguido de un pase de cultivador de campo en la primavera), labranza mínima (un pase de una herramienta de labranza vertical en la primavera), y cero labranza (aplicación PRE de paraquat). Cada sistema de labranza también recibió uno de dos programas de herbicidas; aplicación PRE de flumioxazin (0.09 kg ai ha −1 ) fb glufosinate POST (0.59 kg ai ha −1 ) más S -metolachlor (1.39 kg ai ha −1 ), o sólo aplicaciones POST de glufosinate (0.59 kg ha −1 ). El sistema de labranza profunda resultó en una reducción de 62, 67, y 73% en la emergencia de Amaranthus cuando se comparó con los sistemas de labranza convencional, mínima, y cero, respectivamente. El programa con un herbicida residual también resultó en una reducción de 87% en la emergencia de especies Amaranthus al compararse con el programa de sólo herbicidas POST. El sistema de labranza profunda, combinado con el programa residual, resultó en una reducción de 97% en la emergencia de especies de Amaranthus cuando se comparó con el sistema de labranza mínima combinado con el programa de sólo herbicidas POST, el cual tuvo la mayor emergencia de Amaranthus . Muestras de suelo tomadas antes de la siembra y la aplicación de herbicidas revelaron que en el sistema de labranza profunda solamente 28% de las semillas de Amaranthus fueron localizadas en los 5 cm de suelo superiores del perfil del suelo comparado con 79, 81, y 77% en los sistemas de labranza convencional, mínima, y cero. En general, el uso de labranza profunda con el programa de herbicida residual brindó la mayor reducción en la emergencia de especies de Amaranthus, lo que provee una herramienta útil para el manejo de especies de Amaranthus resistentes a herbicidas cuando sea apropiado.